Borsa Istanbul as an Inflation Hedge: A Post-COVID-19 Perspective - Ozdurak, Caner; Çipe, Bilge; Ertem, Guzem Yilmaz; Bolgun, Kaan Evren (International Journal of Economics and Financial Issues, 2025)
This study delves into the intricate relationship between inflation and stock prices on Borsa Istanbul, with a particular focus on the turbulent post- COVID-19 era. While traditional assets like real estate have historically served as reliable inflation hedges, the emergence of Borsa Istanbul as a potential alternative warrants investigation, especially during the period 2019-2023. To assess the effectiveness of the Turkish stock market as an inflation hedge, we employ a rigorous econometric framework that extends beyond broad market indices to examine sector-specific responses. By adopting a Vector Autoregression (VAR) model, we capture the dynamic interplay between inflation and stock returns. Our analysis incorporates a comprehensive set of macroeconomic control variables spanning the period 2006Q1-2023Q4 and utilizes robust estimation techniques to account for potential structural breaks induced by the COVID-19 pandemic and unconventional economic policies. The primary objective of this study is to determine whether Borsa Istanbul stocks constitute an effective inflation hedge. In essence, our results suggest that the Turkish equity market has served as a safe haven for investors during inflationary periods. A deeper understanding of the relationship between inflation and equity markets is crucial for investors, policymakers, and financial market participants seeking to comprehend and manage inflation risks in emerging economies. In this context the study contributes to existing literature by providing empirical evidence on the inflation hedging capabilities of Borsa Istanbul stocks, particularly in the context of recent economic and geopolitical upheavals.